Urban phenological studies – Past, present, future. (August 2015) - Jochner, Susanne; Menzel, Annette
Abstract: Phenology is believed to be a suitable bio-indicator to track climate change. Based on the strong statistical association between phenology and temperature phenological observations provide an inexpensive means for the temporal and spatial analysis of the urban heat island. However, other environmental factors might also weaken this relationship. In addition, the investigation of urban phenology allows an estimation of future phenology from current information since cities with their amplified temperatures may serve as a proxy for future conditions. Nevertheless, the design of spatial compared to long-term studies might be influenced by different factors which should be taken into consideration when interpreting results from a specific study. In general, plants located in urban areas tend to flush and bloom earlier than in the countryside. What are the consequences of these urban–rural differences? This review will document existing findings on urban phenology and will highlight areas in which further research is needed. Highlights: Urban phenology can be used for the estimation of the urban heat island effect. Confounding factors weaken the phenology–temperature relationship. Urban phenology is useful as a proxy for climate change impacts on phenology. Differences in the study design hinder the generalisation of one specific method. Urban–rural variations in phenology affect vegetation, meteorology, human health. Abstract : Studies on urban phenology can be used to detect urban heat islands and to assess climate change impacts but it still remains important to adequately link spatial and long-term data.